Case Report: Kaposiform Hemangioendothelioma With Spinal Involvement - Qiu, Tong; Yang, Kaiying; Dai, Shiyi; Chen, Siyuan; Ji, Yi (Frontiers in Pediatrics, 2021)
Introduction: Kaposiform hemangioendothelioma (KHE) is a rare, locally invasive vascular tumor that mostly appears in infants and adolescents. KHE with spinal involvement is extremely rare. The aim of this study was to review the imaging features, clinical manifestations and treatment of KHE patients with spinal involvement. Materials and Methods: We reviewed patients with KHE who were admitted to Pediatric Surgery of West China Hospital of Sichuan University from April 2014 to August 2020, and the cases were evaluated. Results: Seven patients with spinal involvement were enrolled in the study, including four (57.1%) males and three (42.9%) females. The age at onset ranged from 1.0 day to 4.0 years, with an average of 1.6 years. Five (71.4%) had pain due to bone destruction, three patients (42.9%) had decreased range of motion (ROM), four (57.1%) patients had scoliosis, two (28.6%) patients developed claudication, and three patients (42.9%) presented with a soft tissue mass in the neck of the back. Five patients (71.4%) had the Kasabach-Merritt phenomenon (KMP), with a minimum platelet value of 8×109/L. All patients were treated with sirolimus, and showed regression of the lesion and/or normalization of the hematologic parameters. Conclusion: KHE with spinal involvement is difficult to diagnose due to its rarity and variable symptoms, which need to be recognized to start early treatment. The management of KHE with spinal involvement should be performed by a multidisciplinary team. Sirolimus can improve outcomes in patients with KHE with spinal involvement.